Harvest maturity, storage conditions and tree age influencing internal browning and fruit quality of Rosy Glow apple (Malus domestica Borkh) - Doe, James Wonder (Stellenbosch : Stellenbosch University, 2020)
Thesis (MScAgric)--Stellenbosch University, 2020.